Temeljni razlikovalni elementi grafičnih sestavov in njihov delež pri oblikovanju različnih fonetično-morfoloških sistemov v Levakovićevih in Paštrićevih glagolskih izdajah - Babič, Vanda (Slavistična revija, 1998)
In the article author delineates two different graphic bases in the Roman editions of Croatian liturgical books from the first half of the 17th c. The 1631 missal is based on the Croatian Glagolitic tradition, while the graphic system of the 1648 breviary is based on the Cyrillic alphabet and the East Slavic orthographic norm, established after the second South-Slavic influence.
Keywords: 17.st.; breviarji; glagolica; hrvaščina; misal; zgodovinski pregledi